2021
DOI: 10.1101/2021.08.23.457333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asymmetric depth-filtration – a versatile and scalable approach for isolation and purification of extracellular vesicles

Abstract: A novel asymmetric depth filtration (DF) approach for isolation of extracellular vesicles (EVs) from biological fluids is presented, and its performance is compared with established methods. The developed workflow is simple, inexpensive, and relatively fast. Compared with ultracentrifugation and size-exclusion chromatography, the developed method isolates EVs with higher purity and yield. Only standard laboratory equipment is needed for its implementation, which makes it suitable for low-resource locations. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…The team demonstrated that DF outperforms ultracentrifugation and SEC in terms of isolation purity and yield. [63] Therefore, this new technique may be used for both diagnostics and EV research.…”
Section: Filtration and Size Exclusion Chromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…The team demonstrated that DF outperforms ultracentrifugation and SEC in terms of isolation purity and yield. [63] Therefore, this new technique may be used for both diagnostics and EV research.…”
Section: Filtration and Size Exclusion Chromatographymentioning
confidence: 99%
“…This approach is simple, fast, inexpensive and does not require specialized equipment. This method was first proposed by Chernyshev et al [63] In a single-step procedure, plasma was diluted in 1:50 Phosphate-buffered saline, centrifuged at 4500g for 30 min at 4°C, and the supernatant was collected and filtered through a 0.8 μm filter. The collected sample was then concentrated by centrifugation at 3500g using a 100 kDa MWCO filter to isolate EVs.…”
Section: Filtration and Size Exclusion Chromatographymentioning
confidence: 99%